Iron Metabolism and Ferroptosis in Epilepsy - Shuang Chen; Shuang Chen; Yongmin Chen; Yongmin Chen; Yukang Zhang; Yukang Zhang; Xi Kuang; Xi Kuang; Yan Liu; Yan Liu; Meiwen Guo; Meiwen Guo; et al. (Frontiers in Neuroscience, 2020)
Epilepsy is a disease characterized by recurrent, episodic, and transient central nervous system (CNS) dysfunction resulting from an excessive synchronous discharge of brain neurons. It is characterized by diverse etiology, complex pathogenesis, and difficult treatment. In addition, most epileptic patients exhibit social cognitive impairment and psychological impairment. Iron is an essential trace element for human growth and development and is also involved in a variety of redox reactions in organisms. However, abnormal iron metabolism is associated with several neurological disorders, including hemorrhagic post-stroke epilepsy and post-traumatic epilepsy (PTE). Moreover, ferroptosis is also considered a new form of regulation of cell death, which is attributed to severe lipid peroxidation caused by the production of reactive oxygen species (ROS) and iron overload found in various neurological diseases, including epilepsy. Therefore, this review summarizes the study on iron metabolism and ferroptosis in epilepsy, in order to elucidate the correlation between iron and epilepsy. It also provides a novel method for the treatment, prevention, and research of epilepsy, to control epileptic seizures and reduce nerve injury after the epileptic seizure.